Effect of Low-Dose Hormone Therapy on Metabolic Parameters and Bone Mineral Density - Atlihan, Ufuk; Yavuz, Onur; Avsar, Huseyin Aytug; Ata, Can; Bildaci, Tevfik Berk; Erkilinc, Selcuk (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Early menopause causes several health concerns that are related directly to the deficiency of ovarian hormones, especially estrogen insufficiency. The purpose of the research was to investigate the impact of low-dose hormone therapy on metabolic parameters and bone densitometry in patients with early menopause. STUDY DESIGN: A total of 98 patients aged 38-42 years with an early-menopause and followed up were evaluated retrospectively in this cohort study. After the diagnosis of early menopause, combined oral contraceptive (COC) treatment including 3 mg Drospirenone + 0.02 mg Ethinylestradiol was recommended to the patients. After 1 year of COC treatment, metabolic, ultrasonographic, and bone densitometry measurements of patients who did and did not use COC regularly were compared. RESULTS: At the 12th-month follow-up, endometrial thickness was significantly higher in the COC group (3.8±0.4 mm) compared with the non-COC group (3.5±0.4 mm) (p<0.01). At the 12th month follow-up, the estradiol value was significantly higher (16.1±1.5 pg/mL) in the COC group compared with the non-COC group (14.8±2.5 pg/mL) (p<0.01). At the 12th month follow-up, the total cholesterol value was found significantly lower in the COC group (197±24.2 mg/dL) compared with the non-COC group (211±28 mg/dL) (p<0.01). At the 12th month follow-up, the Z-score was found significantly higher in the COC group (0.02±0.3) compared with the non-COC group (0.2±0.3) (p<0.01). CONCLUSION: Hormone replacement therapy is very important for women who enter early menopause, and adequate estrogen therapy must be taken to maintain bone density and reduce menopausal symptoms.